In the book "The rise and development of the theory of series up to the early 1820s", the author mentions a paradox that is sometimes known as Poisson Paradox.

$$(2\cos(x))^{m}=\sum_{n=1}^{\infty} \binom{m}{k}\cos(m-2k)x $$

The author wrote that: "In his [1811], Poisson showed that one contradiction derived from the substitution $m=\frac{1}{3}$ and $x=\pi$, Indeed, from $(2\cos(x))^{m})$ it was possible to obtain the three complex values:

$2^{1/3}\frac{1+\sqrt{-3}}{2}$, $-2^{1/3}$, $2^{1/3}\frac{1-\sqrt{-3}}{2}$

whereas the series gave the value $-2^{1/3}$. According to Poisson, the problem arose from the fact that, when $m$ is a rational number, the series

$$\sum_{n=1}^{\infty} \binom{m}{k}\cos(m-2k)x $$

only represented the real part of the expansion $(2\cos(x))^{m}$

I have consulted the work of Poisson and here is how he expands it.

He lets $u=\cos(x)+i\sin(x)$, $v=\cos(x)-i\sin(x)$



He then expands the left hand side according to the binomial formula. The expansion is blurred out in the original text so if someone can help me to reconstruct the series, I will appreciate it.

My question is:

1) How does one obtain the binomial expansion of $(2\cos(x))^{m}$

2) How does one obtain those three complex values from the series?

3) How does this represent a paradox in the theory of infinite series?

Poisson's original article is here page 212-217: https://books.google.com/books?id=IZytoPqRRTMC&pg=PA495&lpg=PA495&dq=Correspondance+sur+l%27%C3%89cole+polytechnique+janvier+1811&source=bl&ots=ivbxKUVHqO&sig=ACfU3U2_3gQyUxL9M_SRJCRG_MXdnPKlwA&hl=en&sa=X&ved=2ahUKEwiex8mHpqXgAhXKl-AKHerWDg8Q6AEwDnoECAEQAQ#v=onepage&q&f=false

Thank you!

  • $\begingroup$ You have a typo in the equation. n is summed but does not appear in the summation. $\endgroup$ – Thomas Feb 7 at 7:26

We define $$R_m(x)=\sum_{n\geq0}{m\choose n}\cos\left[(m-2n)x\right]$$ And $$S_m(x)=\sum_{n\geq0}{m\choose n}e^{i(m-2n)x}$$ So we see that $$R_m(x)=\text{Re}\,S_m(x)$$ Then we see that $$S_m(x)=e^{imx}\sum_{n\geq0}{m\choose n}e^{-2inx}$$ Then we recall that $$(x+1)^a=\sum_{n\geq0}{a\choose n}x^n$$ So we see that $$S_m(x)=e^{imx}\left[\left(e^{-2ix}+1\right)^m\right]$$ $$S_m(x)=\left(e^{ix}+e^{-ix}\right)^m$$ $$S_m(x)=2^{m}\cos(x)^m$$ So we have that $$R_m(x)=(2\cos x)^m$$ If we plug in $m=1/3$ and $x=\pi$, we get $$R_{1/3}(\pi)=\sqrt[3]{2}$$ And I assume that the three values are the three complex roots of $\sqrt[3]{2}$. To find these we recall the formula $$z^{1/n}=\sqrt[n]{|z|}\exp\left[\frac{i}{n}(2\pi k+\arg z)\right],\qquad k=0,1,...,n-1$$ Setting $z=2$ and $n=3$, we have that $|z|=2$ and $\arg z=0$ which qives $$2^{1/3}=\sqrt[3]{2}\exp\frac{2i\pi k}3$$ for every $k=0,1,2$. So, using $e^{ix}=\cos x+i\sin x$, we have that the three complex roots of $2^{1/3}=\sqrt[3]{2}$ are given by $$2^{1/3}\frac{1+i\sqrt3}2,2^{1/3}, -2^{1/3}\frac{1-i\sqrt3}2$$ as desired.

  • 1
    $\begingroup$ Seems OP had a typo and the sum should be $\sum_{\color{red}{n\ge 0}}\dots$ $\endgroup$ – Mike Earnest Feb 6 at 20:59
  • $\begingroup$ @MikeEarnest Sweet! that actually helps a lot $\endgroup$ – clathratus Feb 6 at 21:00
  • $\begingroup$ Note that the issue is precisely that $a^m b^m \neq (a b)^m$. Because of this, $S_m(x) \neq 2^m \cos^m x$ (if you're working with single-valued functions). $\endgroup$ – Maxim Feb 7 at 1:42
  • $\begingroup$ $2^{m}cos^{m}x$ is how it is written in the original document. $\endgroup$ – James Warthington Feb 7 at 2:34
  • $\begingroup$ @JamesWarthington They're the same: $$(2\cos x)^m=2^m\cos^mx=2^m\cos(x)^m$$ it's just different totation $\endgroup$ – clathratus Feb 7 at 2:49

Let $z^m$ be defined as $z^m = e^{m \ln z}$, where $\ln$ is the principal value of the logarithm. Then, assuming $x$ and $m$ are real, $$(e^{i x})^m = e^{i m \arg e^{i x}},$$ which is not necessarily the same as $e^{i m x}$.

For the same reason, assuming that the sums converge, $$\sum_{k \geq 0} \binom m k a^k b^{m - k} = b^m \sum_{k \geq 0} \binom m k \left( \frac a b \right)^k = b^m \left( 1 + \frac a b \right)^m$$ is not necessarily the same as $(a + b)^m$.

We can write $$(2 \cos x)^m = (e^{i x} + e^{-i x})^m = \sum_{k \geq 0} \binom m k e^{i (m - k) x} e^{-i k x} = \\ \sum_{k \geq 0} \binom m k \cos \,(m - 2 k) x + i \sum_{k \geq 0} \binom m k \sin \,(m - 2 k) x$$ or $$(2 \cos x)^m = (e^{-i x} + e^{i x})^m = \sum_{k \geq 0} \binom m k e^{-i (m - k) x} e^{i k x} = \\ \sum_{k \geq 0} \binom m k \cos \,(m - 2 k) x - i \sum_{k \geq 0} \binom m k \sin \,(m - 2 k) x$$ only if we pick $x$ and $m$ for which the intermediate steps are valid. If $m \not \in \mathbb Z$, then $(e^{i x})^m = e^{i m x}$ can be used if $x \in (-\pi, \pi]$ and $(a b)^m = a^m b^m$ can be used if $\arg a + \arg b \in (-\pi, \pi]$.

  • $\begingroup$ I am lost in these comments. I haven't learnt complex exponential so my knowledge is so limited. Thank you though. $\endgroup$ – James Warthington Feb 7 at 19:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.